High-altitude environments enhance the ability of Eothenomys miletus to regulate body mass during food limitation, with a focus on gut microorganisms and physiological markers - Zhang, Tianxin; Jia, Ting; Zhu, Wanlong; Fan, Lixian (Frontiers in Microbiology, 2024)
Animals’ digestion, energy metabolism, and immunity are significantly influenced by interactions between the gut microbiota and the intestinal environment of the host. Previous studies have shown that gut microbiota of Eothenomys miletus can respond to environmental changes, high fiber or fat foods. But how E. miletus in high-altitude adapt to their environment through gut microbiota and physiological changes during winter food shortages period was unclear. In the present study, we evaluated the altitude differences in gut microbiota and their interactions with physiology in terms of body mass regulation in order to study the adaptation of the gut microbiota and physiological indicators of the E. miletus under food restriction settings. E. miletus were collected for this study from Jingdong County (JD, low-altitude) and Xianggelila County (XGLL, high-altitude) in Yunnan Province, China, and split into three groups: control group, food-restricted feeding group for 7 days, and re-feeding group was offered a standard diet for 14 days. 16S rRNA gene sequencing and physiological methods were used to analyze the abundance and community structure of gut microbiota, as well as physiological indicators of each group in E. miletus. The results showed that while the RMR changed more during the period of food restriction, the body mass and major organ masses of E. miletus from high-altitude changed less. After food restriction, RMR in XGLL decreased by 25.25%, while that of in JD decreased by 16.54%. E. miletus from the XGLL had gut bacteria that were more abundant in Firmicutes and had fewer OTUs, and the microbiota had a closer interaction with physiological indicators. Moreover, the gut microbiota adapted to the food shortage environment by enhancing the genera of Bacterroides, Ruminococcus, Turicibacter, and Treponema to improve the utilization of nutrient resources. The interactions between microbial species and the equilibrium of energy homeostasis were further impacted by alterations in physiological indicators and microbial community structure. These variations were important for E. miletus to adapt to the fluctuations and changes of food resources in high-altitude region, which also expand our knowledge of organismal adaptations and the mechanisms behind the interactions between gut bacteria and host physiology.